2020
DOI: 10.4103/ijo.ijo_1327_19
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte to high-density lipoprotein and neutrophil-to-lymphocyte ratios in patients with acute central serous chorioretinopathy

Abstract: Purpose: To investigate monocyte to high-density lipoprotein (HDL) ratio (MHR) and neutrophil-to-lymphocyte ratio (NLR) as indicators of systemic inflammation in acute central serous chorioretinopathy (CSC). Methods: The HDL levels, hematological profiles, erythrocyte sedimentation rates (ESR), and C-reactive protein (CRP) levels of 38 patients with acute CSC (Group I) and 38 controls without CSC (Group II) were measured. Results: MHRs were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Researchers have recently reported that the ratio of monocyte count to HDL (MHR) can be used as an inflammatory index (14)(15)(16). There are only a few studies evaluating the role of MHR in PCOS patients (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have recently reported that the ratio of monocyte count to HDL (MHR) can be used as an inflammatory index (14)(15)(16). There are only a few studies evaluating the role of MHR in PCOS patients (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article by Sirakaya et al on monocyte to high-density lipoprotein ratio (MHR) in acute central serous chorioretinopathy (CSC). [ 1 ] MHR has emerged as a biomarker of inflammation and oxidative stress in recent years. Authors excluded patients with ocular or systemic inflammation and construed their interpretation based on the skewed MHR.…”
mentioning
confidence: 99%
“…In CSC patients, monocyte to high-density lipoprotein (HDL) ratio (MHR) was found to be higher when compared to healthy controls. [ 2 ] In the patients, MHR elevation was not assessed regarding coronary artery diseases. However, CSC might be considered as a potential risk factor for coronary artery disease in men.…”
mentioning
confidence: 99%